1997
DOI: 10.1046/j.1365-2249.1997.4331451.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA-dependent peripheral T cell receptor (TCR) repertoire formation and its modification by rheumatoid arthritis (RA)

Abstract: SUMMARYOur previous studies have disclosed that the peripheral T cell receptor b (TCRB) gene repertoires of RA monozygotic twins were similar. This suggested that the TCRBV repertoire is controlled primarily by genetic factors. Here, we examine how the combination of HLA and presence of RA influence the peripheral TCRB repertoire. Peripheral blood mononuclear cells from six pairs of healthy monozygotic twins, six pairs of monozygotic twins discordant for RA, and nine siblings of a large family, including three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Finally, when identical twins discordant for RA were studied, their BV BJ repertoires appeared almost identical [8]. However, statistical analysis demonstrated that they were slightly different [9]. Similar results were obtained by Walser-Kuntz et al when comparing the repertoires of HLA-DR matched RA patients and controls [7].…”
Section: Hla-dr Influence On the T Cell Repertoire In Normals And Ra mentioning
confidence: 67%
“…Finally, when identical twins discordant for RA were studied, their BV BJ repertoires appeared almost identical [8]. However, statistical analysis demonstrated that they were slightly different [9]. Similar results were obtained by Walser-Kuntz et al when comparing the repertoires of HLA-DR matched RA patients and controls [7].…”
Section: Hla-dr Influence On the T Cell Repertoire In Normals And Ra mentioning
confidence: 67%
“…The increased percentage of particular Vβ families in ChrRx and LTS patients could reflect a selective expansion of alloreactive and Treg cells as a consequence of persistent exposure to donor alloantigens. Other reports have demonstrated that age [44], autoimmune diseases [45,46] and viral infections [47,48] could also influence the TCR repertoire. We can not be sure whether these factors influenced our results; however, our healthy controls were matched by age with LTS patients and none of them have clinical autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Turbulence of the genetically regulated alp T cell repertoire is inostly attributable to clonal expansions of CD8 cells and, to a lesser extent, those of CD4 cells (49,50). Moreover, a single TCR can potentially interact with several different peptide-MHC complexes.…”
Section: Discussionmentioning
confidence: 99%